EFEKTIVITAS MODEL TREFFINGER DALAM MENGEMBANGKAN DISPOSISI KREATIF DAN KETERAMPILAN BERPIKIR KREATIF SAINS PADA SISWA SEKOLAH DASAR: STUDI LITERATUR REVIEW - Fitriana, Iin Mahlia; Sukarso, AA; Gunawan; Asrin; Subarinah, Sri (Alpatih Harapan Semesta, 2024)
This study aims to analyze the effectiveness of the Treffinger Model in fostering creative disposition and science creative thinking skills in elementary school students through a comprehensive literature review. The study will examine various relevant literature, including scientific journals, books, and research reports, discussing the implementation and impact of the Treffinger Model in science education at the elementary school level. The analysis will focus on how the Treffinger Model can facilitate the enhancement of creative disposition, such as curiosity, openness to new experiences, and a willingness to take risks, as well as science creative thinking skills, such as the ability to ask questions, generate novel ideas, and solve problems creatively. The findings of this analysis are expected to provide valuable insights for educators and researchers in designing more effective science learning strategies to cultivate the creative potential of elementary school student